Komposisi Jenis Makanan dalam Lambung Ikan Nilem (Osteochilus vittatus Valenciennes, 1842) di Danau Tamblingan, Buleleng, Bali - Sathyananta, Kadek Prayuda; Pertami, Nyoman Dati; Kartika, Gde Raka Angga (Journal of Marine and Aquatic Sciences; Vol 9 No 2 (2023)DO - 10.24843/jmas.2023.v09.i02.p14, 2023)
Tamblingan Lake is the smallest lake in Bali and is a confined endorheic basin area that very vital for the surrounding environment. Bonylip barb is a fish from the family Cyprinidae that lives in Tamblingan Lake. Information on the composition of such fish food in Tamblingan Lake does not exist. The aims of this study to analyze and explain the food ecology of Osteochilus vittatus, especially the composition of its food types in Tamblingan Lake. The study was conducted in Tamblingan Lake from January to June 2019 using a modified gill nets with the mesh size 0.5; 1.0; 1.5; 2.0; 2.5; 3.0 inches. The fish was carried out at five stations with water characteristics that represent the water conditions of Tamblingan Lake. The fish was obtained during the research were calculated on 216 individuals. Contents of the intestines were observed using a microscope with the census method without replication. Composition of the type of food was interpreted using Microsoft Excel to be described in a chart. The results showed that Osteochilus vittatus in Tamblingan Lake was omnivore fish with 51 species of organisms found consisting of 7 classes of phytoplankton, 7 classes of zooplankton, and 1 class of aquatic plant. Phytoplankton from the class of Bacillariophyceae was the dominant food of Osteochilus vittatus. The class of Bacillariophyceae that was often found was Surirella sp. The food of Osteochilus vittatus change due to changing seasons. Information of Osteochilus vittatus can be used as a basis for fisheries resources management in Tamblingan Lake.